Adoption Impact of Improved Cowpea Variety in Selected Areas of Chattogram District of Bangladesh - Uddin, M Jamal; Rashid, Md Sami Ur; Begum, M. E. A (International Journal of Sustainable Agricultural Research, 2020)
The study was carried out in 13 villages under three Upazila’s namely Hathazari, Fatikchari and Satkania of Chattogram District, Bangladesh during 2017-18 covering 210 farmers in the selected locations. Results revealed that the rate of adoption of cowpea (BARI Cowpea-1) was found to be higher (71%) than that of the local and mixed varieties. The highest number of the respondents came to know about BARI Cowpea-1 from DAE (58.6%) followed by seed dealers (31.7%), research stations (19.0%) and NGO’s (17.0%). The average yield of BARI Cowpea-1 was recorded at 0.613/ha irrespective to all locations; which indicated that the productivity of this variety has been declined due to perhaps mixed cultivation practices with the local variety, lack of knowledge on modern production technologies, lack of irrigation water during the dry seasons and not using the recommended dose of manures and fertilizers. Thus the adoption rate of individual production technology of BARI Cowpea-1 was found unsatisfactory. But it still might project promises; if the farmers could be acquainted, trained and put in practice with the modern production technologies. The respondents had agreed upon significant positive socio-economic impacts of cowpea cultivation on their livelihoods; so it’s needed to motivate farmers to follow the recommended production technologies for gaining higher yield from this variety or alternatively needs to develop and release new varieties for this region.